Pengaruh E-Promotion, E-WOM dan lokasi terhadap kepuasan konsumen melalui keputusan pembelian sebagai variabel intervening - Dian Citaningtyas Ari Kadi; Hari Purwanto; Linda Dwi Ramadani (MBR (Management and Business Review), 2021)
The purpose of this study was to determine the effect of E-Promotion, E-WOM and location on consumer satisfaction through purchase decisions as intervening variables. The research used is quantitative research with a sample of 384 respondents. Using a 5-point Likert Scale and Path Analysis was used for analysis and hypothesis testing. The findings of this study indicate that E-Promotion, E-WOM and location have an effect on consumer satisfaction and purchase decisions. While other findings Purchase Decisions act as a mediation of the relationship between E-Promotion, E-WOM and location on consumer satisfaction. For further research, it is possible to enter the buying interest variable.